Kombinasi Ekstrak Rimpang Jahe dengan Insektisida Fipronil untuk Pengendalian Hama Trips pada Kacang Hijau - Indiati, S. W. (Jurnal Penelitian Pertanian Tanaman Pangan, 2014)
Thrips, Megalurothrips usitatus is an important pest on mungbean. Severe attack by thrips causes yield losses up to 64%. Control measure by combining the use of botanical and synthetic insecticides is expected to reduce the amount use of synthetic insecticides. The research was aimed to obtain the proper time and frequency applications of botanical and synthetic insecticides, most effectively control the thrips on mungbean. The research was conducted at Muneng research station during dry season of 2012. The treatment were arranged on randomized block design, three replications of 10 treatments. New mungbean varieties, Vima-1 was planted on plot of 20 m x 3 m, with 40 cm x 15 cm spacing, two plants per hill. Fertilization of 45 kg Urea + 45 kg SP36 + 50 kg KCl/ha were applied at planting. Observations were made on thrips populations, damages caused by thrips attack, grain yield and yield components. Results showed that the use of fipronil 2 ml/l at 10 days after planting (DAP) followed by application of ginger rhizome extract 20 g/l at 17; 24; 31 DAP and the use of fipronil 2 ml/l at 10 and 17 DAP followed by application of ginger rhizome extract 20 g/l at 24 and 31 DAP effective to control thrips, equivalent with the use of fipronil 2 ml / l at 10; 17; 24; 31 DAP . The use of ginger extract as botanical insecticide reduces the use of synthetic insecticide thus maintains the quality of environment by reducing the insecticide residue.